Assessment of the New 2012 EULAR/ACR Clinical Classification Criteria for Polymyalgia Rheumatica: A Prospective Multicenter Study - ALİBAZ ÖNER, FATMA; YAĞCI, İLKER; DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2016)
Objective. To assess the performance of the new 2012 provisional European League Against Rheumatism (EULAR)/ American College of Rheumatology (ACR) polymyalgia rheumatica (PMR) clinical classification criteria in discriminating PMR from other mimicking conditions compared with the previous 5 diagnostic criteria in a multicenter prospective study. Methods. Patients older than 50 years, presenting with new-onset bilateral shoulder pain with elevated acute-phase reactants (APR), were assessed for the fulfillment of the new and old classification/diagnostic criteria sets for PMR. At the end of the 1-year followup, 133 patients were diagnosed with PMR (expert opinion) and 142 with non-PMR conditions [69 rheumatoid arthritis (RA)]. Discriminating capacity, sensitivity, and specificity of the criteria sets were estimated. Results. Discriminating capacity of the new clinical criteria for PMR from non-PMR conditions and RA as estimated by area under the curve (AUC) were good with AUC of 0.736 and 0.781, respectively. The new criteria had a sensitivity of 89.5% and a specificity of 57.7% when tested against all non-PMR cases. When tested against all RA, seropositive RA, seronegative RA, and non-RA control patients, specificity changed to 66.7%, 100%, 20.7%, and 49.3%, respectively. Except for the Bird criteria, the 4 previous criteria had lower sensitivity and higher specificity (ranging from 83%-93%) compared with the new clinical criteria in discriminating PMR from all other controls. Conclusion. The new 2012 EULAR/ ACR clinical classification criteria for PMR is highly sensitive; however, its ability to discriminate PMR from other inflammatory/noninflammatory shoulder conditions, especially from seronegative RA, is not adequate. Imaging and other modifications such as cutoff values for APR might increase the specificity of the criteria.
Keywords: POLYMYALGIA RHEUMATICA; CLASSIFICATION CRITERIA; RHEUMATOID ARTHRITIS; CITRULLINATED PEPTIDE ANTIBODIES; ERYTHROCYTE SEDIMENTATION-RATE; GIANT-CELL ARTERITIS; TEMPORAL ARTERITIS; DIFFERENTIAL-DIAGNOSIS; FOLLOW-UP; ARTHRITIS; ONSET; ULTRASOUND; SHOULDER